Measurement of Cartilage Deformation in Intact Knee Joints under Compressive Loading - Rashid, Balsam Muqdad; Hamandi, Sadiq Jaafar; Khalil, Eman Ghadban (Al-Nahrain Journal for Engineering Sciences, 2022)
Many joints in the body depend on cartilage for their mechanical function. Since cartilage lacks the ability to self-heal when injured, treatments and replacements for damaged cartilage have been created in recent decades. The mechanical tests had an important role in the treatment and designing of the replaced cartilage. There are two types of cartilages in the knees: fibrocartilage (the meniscus, it is a special type of cartilage) and hyaline cartilage. Its mechanical properties are important because structural failure of cartilage is closely related with joint disorders. This study aimed to determine the stress-strain curve to give broader understanding of the material’s properties. The results of this study could help to develop computational models for evaluating mechanics of knee joint, predicting possible failure locations and disease progression in joints.The study involved two specimens taken from bovine, the first was the articular cartilage with subchondral bone and the second was the meniscus cartilage each one loaded on a compressive testing machine to compute the displacement, and the force applied, enabling the calculation of the stress-strain curve of the material.Specimen failure occurred in the articular cartilage surface at a force break of 73.8N and get force peak about 87.2 N. The meniscus cartilage failure had occurred at a force break of 29.2 N and get force peak about 34.9 N.